2018
DOI: 10.1590/0102-311x00219617
|View full text |Cite
|
Sign up to set email alerts
|

Association between the employment status and the presence of depressive symptoms in men and women in Mexico

Abstract: Association between the employment status and the presence of depressive symptoms in men and women in MexicoAsociación entre el estatus de empleo y la presencia de síntomas depresivos en hombres y mujeres en México Associação entre situação laboral e presença de sintomas depressivos em homens e mulheres mexicanos AbstractThis study aims to estimate the relationship between employment status and depressive symptoms among Mexican adults, as well as to explore its differential effect by gender. Cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
1
0
1
Order By: Relevance
“…That might be due to the fact that there was a diversity in the age group of the study participants as there were students, workers and unemployed enrolled in the study. In support of our results, a study conducted in Mexico concluded that employment status is not associated with the presence of depressive symptoms in women [24]. In contrast, A study took a place in Canada focused on social determinants of mental showed that being unemployed impacts the health primary health care centers.…”
Section: Employment Statussupporting
confidence: 83%
“…That might be due to the fact that there was a diversity in the age group of the study participants as there were students, workers and unemployed enrolled in the study. In support of our results, a study conducted in Mexico concluded that employment status is not associated with the presence of depressive symptoms in women [24]. In contrast, A study took a place in Canada focused on social determinants of mental showed that being unemployed impacts the health primary health care centers.…”
Section: Employment Statussupporting
confidence: 83%
“…That might be due to the fact that there was a diversity in the age group of the study participants as there were students, workers, and unemployed enrolled in the study. In support of this, a study conducted in Mexico concluded that employment status is not associated with the presence of depressive symptoms in women [19]. In contrast, a study conducted in Canada that focused on social determinants of mental health showed that being unemployed impacts the health of individuals, including mental health.…”
Section: Discussionmentioning
confidence: 98%
“…Hiç eğitimi olmayan kişilerde %7, ilkokul mezunlarında %38, ortaokul mezunlarında %41, üniversite mezunlarında ise %8 oranında depresyon görüldüğünü belirtmişlerdir. [49] Bu çalışmadan da anlaşılacağı üzere hiç eğitim almamış kişilerde farkındalığın az olması depresyona karşı koruyucu olabilir. Eğitim düzeyinin artışıyla ise depresyon tanısı ve tedavi arayışıyla bu sıklık azalabilir.…”
Section: Etik Onayunclassified